Examining the impact of thought substitution on intentional forgetting in induced and naturally occurring dysphoria. (30th July 2016) - Noreen, Saima; Ridout, Nathan
Abstract: Two experiments were conducted to determine if natural and induced dysphoria is associated with impaired forgetting and, whether a thought-substitution strategy would ameliorate any observed deficits. Study 1: 36 dysphoric & 36 non-dysphoric participants learnt a series of emotional word pairs. Participants were subsequently presented with some of the cues and were asked to recall the targets or prevent the targets from coming to mind. Half of the participants were provided with substitute words to recall instead of the original targets (aided suppression). At final memory testing, participants were asked to recall the targets to all cues. Dysphoric participants exhibited impaired forgetting, even when using a thought substitution strategy. Non-dysphoric participants, however, were able to use substitutes to suppress words. Study 2: 50 healthy participants initially completed the aided condition of the forgetting task. Participants were then given a positive or negative mood-induction, followed by another version of the forgetting task. Although all participants showed a forgetting effect prior to the mood-induction, only the positive group was successful at forgetting after the mood induction. Taken together, these findings do not support the utility of thought-substitution as an aid to forgetting in individuals in a naturally or induced dysphoric mood. Highlights: Dysphoric participants exhibited impaired forgetting of emotional words. Individuals induced in a negative mood exhibited impaired forgetting. Impaired forgetting was found, even when using a thought substitution strategy. Depression severity was associated with poorer forgetting. There was no evidence of a specific deficit in forgetting depression-relevant words.